ESTIMASI PROYEKSI PENYEDIAAN BERAS DI KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
This research is an Estimation of Projection of Rice Supply in Ogan Komering Ulu District. This study aims to estimate the projected supply of rice available in each District in Ogan Komering Ulu District in 2018 - 2022. The research sites are District in Ogan Komering Ulu. The research method used is library research. The type of data used in this study is secondary data. The data processing method used is using exponential growth analysis. The results showed that the estimated projection of the supply of rice in 2018-2022 would have a surplus in 4 Subdistricts namely Pengandonan District, Muara Jaya District, Ulu Ogan District and Semidang Aji District, and would experience a deficit in 6 Sub-Districts namely Sosoh Buay Rayap District, Review, Sinar Peninjaun, Lubuk Batang, Lubuk Raja, West Baturaja, and in 3 Districts there will be deficits and surpluses, namely Lengkiti District, East Baturaja District and Kedaton Peninjauan Raya District. Keyword: Rice Production, Rice Consumption, Rice Suplly.